Are Social Marketing and Advertising Communications (SMACs) Meaningful?: A Survey of Facebook User Emotional Responses, Source Credibility, Personal Relevance, and Perceived Intrusiveness. Issue 2 (2nd July 2016) - Morris, Jon D.; Choi, Yunmi; Ju, Ilyoung
ABSTRACT: As users of social networking sites increase, placing ads on social network site (SNS) platforms is necessary for the medium and the advertiser. This placement does not come without significant concerns the impact of diverse social marketing and advertising communications. To provide a deeper understanding of the feelings of SNS users to marketing and advertising communications, this study measured the emotional responses in the three-dimensional form of appeal, engagement, and empowerment . The study also examined the cognitive or rational variables personal relevance, perceived intrusiveness, and source credibility, to determine their effect and relationship to emotional response on social marketing and advertising communications (SMACs) on Facebook. An online survey among college students revealed that more positive emotional and rational responses were generated toward SMACs that Facebook users re-promoted than toward those SMACs that are directly promoted by marketers. The re-promoted marketing communications appeared as less intrusive and more credible than those that are marketer promoted.